Music from 0 to 3 years old (Journal of Parents and Teachers, 1995)
The mother interacts with the baby through vocalizations of the letter “A”, varying intonations and encouraging dialogue. Sensory activities are also performed, such as listening to the rain, taking care that the baby does not hit the glass.
Keywords: music and education; intonations; dialogue; sensory activities